Levantamento de tratamento de dor endodôntica, realizado em pronto atendimento odontológico: necessidade de protocolo - Trizzi, Juliana Quintino [UNESP] (2020)
Endodontic pain affects a large part of the world population, which leads for a seek for urgency treatment. Few reports studied the casuistry and protocol of dental care inserted in the prompt attendance, such as: diagnosis, provisional coronal sealing, intracanal medication, systemic medication and patient with pain complaint. The objective of this study was to carry out a survey of the urgency protocol in both dental care institutions: Prompt Dental Care Services of Araçatuba city (PAO) and the Araçatuba School of Dentistry/Sao Paulo State University Júlio de Mesquita Filho (FOA/UNESP). The medical records of patients who voluntarily sought care in the urgency department, with anamnesis and a description of the performed procedure, were evaluated. Data such as intracanal medication, coronary sealing, systemic medication and patient return with pain complaint were tabulated and statistically evaluated via SigmaPlot 13.0 software, with no association of these variables and the patient return with pain complaint (P> 0.05). However, association (P<0.05) was observed between attendance institution where urgency was carried out and the presence of temporary coronal sealing in cases with abscess, whereas FOA performs the coronal sealing as attendance protocol and PAO doesn’t. There was also an association (P<0.05) between diagnosis, prescription of systemic medication and dental care attendance institution, since PAO performed the largest number of medication prescriptions. It is concluded that, although dental care attendance protocols were similar in cases of pulpitis or necrosis, differing only in abscess, the main objective of urgency treatment was achieved in both treatment protocols, since treated patients were painless for more than 7 days